Electrochemical processes at gold ∣ thiourea-containing aqueous acid solution interfaces - Bolzán, Agustín Eduardo (2003)
The electrochemical behaviour of thiourea (TU) on gold in acid solutions is investigated in the range −0.2 to 1.7 V (versus standard hydrogen electrode) by conventional and triangularly potential modulated voltammetry, rest potential (Erest) measurements, rotating disk and rotating ring-disk techniques. The value of Erest is determined by an electrochemical reaction involving formamidine disulphide (FDS), adsorbed TU and soluble [Au(TU)2]+ species. For TU concentrations (cTU) in the range 1⩽cTU⩽50 mM, Erest decreases linearly with log cTU with a slope of approximately −0.090 V decade−1, while in the range 0.1⩽cTU⩽0.25 mM, it approaches −0.120 V decade−1. Conventional and triangularly modulated voltammetry data indicate the quasi-reversible adsorption of TU occurring in the range −0.2⩽E⩽0.1 V, and the electro-oxidation of TU to FDS in the range 0.2⩽E⩽0.9 V, occurring simultaneously with the electrodissolution of gold yielding soluble [Au(TU)2]+ species. Both the electro-oxidation of TU and the electrodissolution of gold are under mass transfer control influenced by adsorbate formation. Different adsorbates from TU are produced depending on the adsorption potential and time. The electro-oxidation of these adsorbates in the range 0.9–1.7 V yields sulphate, carbon dioxide and CN residues. Reaction products are consistent with previous STM and FTIRS data. Comparative electrochemical data from FDS- and sulphide-containing solutions are also presented. Reaction pathways in which the participation of different adsorbates is considered, are discussed.